Assessment of genetic diversity in Ganoderma lucidum using RAPD and ISSR markers - PREM NATH SHARMA; BRIJ MOHAN SHARMA, RENU THAKUR, POOJA KAPOOR* (Indian Phytopathology, 2015)
Genetic diversity of 31 isolates of Ganoderma lucidum from different hosts and geographic regions were analyzed using RAPD and ISSR markers. Ten polymorphic RAPDs were selected from 156 primers along with 8 polymorphic universal ISSR primers. RAPD and ISSR exhibited polymorphism of 88.2 and 78.8 per cent, respectively. RAPD markers, viz. S-1005, OPF-6 exhibited maximum polymorphism (93.3%) whereas ISSR- 833 showed maximum of 89.6 per cent polymorphism. Cluster analysis of 31 isolates/strains of G. lucidum grouped isolates in 4 subpopulation at 42 per cent (RAPD) and 5 subpopulation using ISSR markers at 40 per cent similarity coefficient. Multilocus ISSR primers clustered isolates based on their geographical origin to considerable levels and exhibited fair similarities among grouping of isolates having sessile/short stalk length than those having long stalk. Therefore, this study reports the high level of genetic diversity of Ganoderma lucidum from North Western Himalayas using both RAPD and ISSR techniques.